The design and development of China sports scientific research cooperation platform base on e-science paradigm - Ma, Y.; Suna, J. (Procedia Engineering, 2012)
E-science research is a new research collaboration pattern emerging in the information age. Compared with traditional research methods, E-science provides great developing space for the sharing and exchanging of scientific research. This paper illustrates a B / S structure based method of designing and implementing sports science collaboration platform applying E-science theory. The platform originates from sports research reality, whose function modules include first page, scientific research progress, research program collaboration, personal zone, research collaboration tools, management of academic meeting, research information online, sharing scientific apparatus, questionnaire, and systematic management. The platform solves key techniques concerning sports researchers` scientific research project cooperation, scientific research resources integration, scientific research process control, and provides the possibility to sports researchers for scientific cooperation and innovation.